Public goods and public bads. (8th May 2018) - Buchholz, Wolfgang; Cornes, Richard; Rübbelke, Dirk
Abstract: In many empirically relevant situations agents in different groups are affected by the provision of a public characteristic in divergent ways. Whereas for one group it represents a public good, it is a public bad for another group. Applying Cornes and Hartley's aggregative game approach, we analyze a general model in which such contentious public characteristics are present and are provided cooperatively. In particular, we establish neutrality results with respect to redistribution and growth of income, infer the effects of preference changes and coalition formation, and present a technology paradox. Finally, we compare the outcome of voluntary provision of the contentious public characteristic with the Pareto‐optimal solution, highlighting a potential conflict between equity and efficiency in this case.